NAVIGATING THE LABYRINTH OF SUBJECTIVE CAREER SUCCESS IN THE 21ST CENTURY: A LITERATURE REVIEW - Safin, Siti Zaharah; Jamalurus, Hasmah Laili; Mahshar, Mursyda (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Subjective career success, an individual's own evaluation of their career achievement and satisfaction, is a critical yet immature construct in career research. The literature review addresses the lack of consensus regarding its measurement and conceptualization by synthesizing findings from 50 Scopus peer-reviewed articles (2010–2024). The study identifies determinants of subjective career success, including personal values, proactive behaviors, interpersonal relationships, and cultural contexts. Recognition, job satisfaction, and meaningful work are significant consequences. Despite these observations, gaps remain, including the creation of culturally responsive measures and addressing underrepresented populations, such as minorities and women. The overreliance on qualitative analysis, also indicate the need for longitudinal studies and mixed-methods research. The article integrates socio-emotional selectivity theory and the motivational theory of lifespan development to explain how subjective career success evolves across life stages. The findings provide action plans for organizations and individuals, emphasizing the importance of aligning personal values with career goals and establishing conducive work environment climates. Future research is suggested to focus on the refinement of measurement instruments, exploring diverse populations, and theory-practice gaps to enhance career satisfaction in dynamic working environments. This review contributes to both theoretical advancement and practice-based insights on subjective career success.